Situational analysis of the Doma-Rutu socio-ecological landscape in Nasarawa State, Nigeria - Igbadun, H. E.; Ojeleye, O. A.; Oke, Adebayo; Atampugre, Gerald; Tilahun, Seifu A.; Ismail, H.; Cofie, Olufunke O.; Mabhaudhi, Tafadzwanashe (International Water Management Institute (IWMI). CGIAR Initiative on West and Central African Food Systems Transformation, 2023)
The CGIAR Initiative on West and Central African Food Systems Transformation (TAFS-WCA) addresses challenges in the food systems of West and Central Africa, characterized by weak institutional arrangements, low productivity, and resource depletion. TAFS-WCA focuses on landscape management in selected countries, aiming for community engagement and the implementation of innovative solutions. The Doma-Rutu socio-ecological landscape in Nasarawa State, Nigeria, was chosen for intervention, with a comprehensive analysis revealing abundant water resources and agriculturally viable areas. However, persistent risks such as land tenure issues, low production capacity, and unsustainable practices threaten the landscape's well-being. Using the DPSIR-SEL Framework, the study assesses Driving forces, Pressures, States, Impacts, and Responses, providing valuable insights for policymakers to address environmental challenges and plan for future sustainability. To address the identified challenges, increased government presence in the landscape is needed to enhance stakeholder inclusiveness, prevent conflicts, and halt landscape degradation. Farmers should be organized and trained in effective water management to sustain the use of floodplains for dry-season farming. Innovative water management techniques and technologies should be considered, such as alternate wetting and drying technology for paddy production and pipe irrigation systems. The vast land under the Doma and Rutu irrigation schemes must be put to productive use during the dry season to minimize degradation caused by leaving it bare. Attention should also be given to raising native tree seedlings to reforest marginal lands exposed to degradation, and technology transfer on floodplain management should be actively pursued. After the harvest of rain-fed crops, open grazing takes place, and the government is recommended to create an enabling environment for controlled open grazing practices in the landscape.